Сто великих мифов и легенд - Муравьева Татьяна Владимировна (Сто великих, 2009)
Экземпляры: ф.8 (2010) / Инвентарный номер: 53209 / Цена: / Сис.шифр: 82.3(0) / Авт.знак: М 91 / ГРНТИ: 17.71 / ББК: 82.3(0)